Oral flora: Protection or destruction of dental tissue - Shakya, Merina; Kayastha, Pujan Kranti; Jioa, Huang (International Journal of Endorsing Health Science Research, 2018)
Background: Oral cavity contains heterogenous environment which provides different niches in different environment present in a symbiotic relation. Normal oral flora when getting favorable environment gets attached to the tooth surface. Alteration in this mutualistic association transforms into diseased condition. The oral cavity begins to harbor microflora immediately after birth. Oral cavity harbors about 20 phyla and more than 700 species. The objective of this study is to determine the origin of the microorganisms responsible for dental diseases. Methodology: PUBMED database was searched for the English articles published with the combinations of following search terms: normal oral bacteria, oral bacteria, oral microbiome, dental caries, tooth caries, endodontic infection, and recurrent pulpal infection. Abstracts and also full text was revised to identify the suitable papers that describe the microbiological association of dental diseases which were used. Results: Nosocomial infection has found to be associated with persistent endodontic infection. Thus, proper sterilization and change of instruments and gloves after each procedure for every root canal instrumentation are mandatory to provide clean sterile preparation of the canal. Also, persistent/secondary intraradicular infection associated with Actinomyces species and P. propionicum is treated with surgical procedure only. Therefore bacteriological analysis of the canal helps to determine the efficacy of the endodontic treatment in primary infection, chances of secondary or persistent endodontic infection, and requirement of surgical treatment. Conclusion: Dental diseases are mainly associated with the virulence of different microorganisms present in the oral cavity. After the initiation of disease, exogenous bacteria are attracted to the site. Thus maintenance of proper oral hygiene prevents the transformation of normal flora to a diseased state. If the disease is diagnosed early and treated, it prevents the life-threatening condition.